Power Flow Analysis of Electrical Network Systems Using Gauss-Seidel Method and Python - Anna Nur Nazilah Chamim; Karisma Trinanda Putra; Muhammad Fahrul Al Farisi (Emerging Information Science and Technology, 2023)
This study aims to analyze the power flow in a 150kV radial power system on the island of Bali, the reason the author uses the Bali island system is because the number of busbars in the system is not too many and the data on the system is known. The problem of this research is limited by determining the voltage, power flow, and power losses in the system. The method used in this study is the Gauss-Seidel method through simulation with the help of Visual Studio Code software and the Python 3.9.2 program. The simulation is carried out by producing a total of 8 iterations. The simulation is carried out to find the parameters of the load voltage, apparent power on the slack bus, current, power flow and power losses on the line. The simulation results show that, under a load condition of 70% of the load transformer capacity, the voltage at the load bus node experiences a voltage drop, reaching 4.48% at bus 10. So when the system operates for generation conditions, the power that can be generated is 1,275.6 MegaWatt of the total generator installed, and the power delivered to each bus node is 2,090 MVa and the power losses in the system are 3.69% of the total power distributed to the bus nodes